Novel selective adsorption cooling materials for heating cigarettes - Chaojian Li; Xiaojuan You; Hongmei He; Huaibin Shi; Xin Gao; Wei Tang (Adsorption Science & Technology)
Heated cigarettes are becoming trendy due to their advantage of not burning the tobacco material and thus reducing the amount of harmful ingredients released, while being able to leave the nicotine and tar content of the smoke untouched. However, the high temperature of the smoke as it enters the human mouth can affect the user experience. Therefore, the development of adsorption cooling materials for use in heated cigarettes is gradually becoming a hot topic. In this work, an adsorption cooling material based on embossed rod powder was prepared. It was found that compared with the commercial Yoga cooling material, the embossed rod powder based adsorption cooling material was able to reduce the maximum smoke temperature to 45.16 °C. In addition, it reduced the adsorption of nicotine by the cooling material, and increased the glycerol and nicotine content in the cooled smoke, which effectively promoted the taste of the smoke. Furthermore, the molecular simulation results found that the higher specific surface area and rich microscopic pore structure could increase the heat conduction area of the high-temperature flue gas, which enhanced the heat transfer effect of the flue gas. Finally, the periodic characteristic velocity pulsation destroyed the boundary layer formed by the fluid in the wall region, which increased the convective heat transfer effect between the fluid and the particles. The optimum sample 03 had the largest specific surface area and the lowest crystallinity, and thus had the best cooling effect. This work could provide some reference significance for the development of cooling materials for heating cigarettes.